2006
DOI: 10.1016/j.apmr.2006.03.019
|View full text |Cite
|
Sign up to set email alerts
|

The Relation Between Previous Fractures and Physical Performance in Elderly Women

Abstract: words: 198Text words (excluding abstract): 2265Graphics: 2 tables, 1 figure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 26 publications
1
12
0
1
Order By: Relevance
“…In four studies, balance was examined among patients with and without vertebral fractures (Table 2). 3,11,41,45 One study also assessed thoracic kyphosis and scored t‐score for BMD 3 . Two studies controlled for visual, vestibular and proprioceptive dysfunctions 3,41 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In four studies, balance was examined among patients with and without vertebral fractures (Table 2). 3,11,41,45 One study also assessed thoracic kyphosis and scored t‐score for BMD 3 . Two studies controlled for visual, vestibular and proprioceptive dysfunctions 3,41 …”
Section: Resultsmentioning
confidence: 99%
“…Gerdhem et al . measured balance during the Romberg test, finding a significantly worse performance of women with vertebral fractures 45 . Greig et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…O envelhecimento gera modificações estruturais e funcionais, comprometendo todos os componentes do controle postural, sensorial, efetor e o processamento central. O equilíbrio é composto pela integração das informações dos sistemas visual, sensorial e proprioceptivo, além da função vestibular e neuromuscular, permitindo a manutenção do controle postural 5 . O avanço da idade é diretamente proporcional à presença de múltiplos sintomas otoneurológicos, tais como vertigem e outras tonturas, perda auditiva, zumbido, alterações do equilíbrio corporal, distúrbios da marcha, quedas ocasionais, entre outros 6,7 .…”
Section: Introductionunclassified
“…[8][9][10] Crosssectional analyses have found that individuals with prior fracture have poorer performance in gait speed, sit-tostand, and balance tests. 11,12 It is not clear whether physical performance impairment is a consequence of fracture or a predisposing factor. 8,9,13 The Safe Functional Motion test (SFM) is a performance-based tool developed by clinicians to evaluate body mechanics and functional motion during a sample set of tasks in people at risk for fragility fracture.…”
mentioning
confidence: 99%